2022
DOI: 10.1038/s41598-022-12540-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of the meningeal lymphatic system in local meningeal inflammation and trigeminal nociception

Abstract: A system of lymphatic vessels has been recently characterized in the meninges, with a postulated role in ‘cleaning’ the brain via cerebral fluid drainage. As meninges are the origin site of migraine pain, we hypothesized that malfunctioning of the lymphatic system should affect the local trigeminal nociception. To test this hypothesis, we studied nociceptive and inflammatory mechanisms in the hemiskull preparations (containing the meninges) of K14-VEGFR3-Ig (K14) mice lacking the meningeal lymphatic system. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 77 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…In this case, we used a more reliable model for testing migraine pathology, such as an ex vivo meningeal preparation [ 17 , 18 ]. This selection was based on the emerging view that meningeal tissues, composed by blood and lymphatic vessels, multiple nerve fibers, and local immune cells, are supposed to be the origin site for migraine pain [ 17 , 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this case, we used a more reliable model for testing migraine pathology, such as an ex vivo meningeal preparation [ 17 , 18 ]. This selection was based on the emerging view that meningeal tissues, composed by blood and lymphatic vessels, multiple nerve fibers, and local immune cells, are supposed to be the origin site for migraine pain [ 17 , 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of IFN-γ on GABAergic neurotransmission and on plasticity were described in hippocampal and prefrontal cortical neurons 22 , 23 , 64 , but we cannot exclude that the effects on GABAergic neurotransmission are mediated by glial cells or perivascular macrophages 65 , 66 . It has been demonstrated that local cytokines in the meningeal niche, such as IL-1 and IL-12, could induce the production of IFN-γ by NK cells 67 , 68 , but further studies will be necessary to better understand the molecular mechanisms that modulate IFN-γ production in the meninges.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells present in the vicinity of meningeal dural blood vessels and have been closely implicated in the modulation of brain function and in migraine development. Notably, recent work shows that early life stress has a profound impact on meningeal inflammation and drives dural mast cell activation, which then promoted anhedonic-like behaviour in mice [ 65 67 ]. However, we have a very little understanding about the nature of the systematic interactions between different subpopulations of dural immune cells, including mast cells, and how altered communication between them can predispose to increased proinflammatory cytokine secretion (e.g., TNF and calcitonin gene-related peptide) and mast cell activation in migraine.…”
Section: New Insights Into Meningeal Immune Composition and Responsesmentioning
confidence: 99%